High glucose causes developmental abnormalities in neuroepithelial cysts with actin and HK1 distribution changes - Peng, Sisi; Wu, Yu; Zheng, Yufang (Frontiers in Cell and Developmental Biology, 2023)
It has been reported that the offspring of diabetic pregnant women have an increased risk for neural tube defects. Previous studies in animal models suggested that high glucose induces cell apoptosis and epigenetic changes in the developing neural tube. However, effects on other cellular aspects such as the cell shape changes were not fully investigated. Actin dynamics plays essential roles in cell shape change. Disruption of actin dynamics is known to cause neural tube defects. In the present study, we used a 3D neuroepithelial cyst model and a rosette model, both cultured from human embryonic stem cells, to study the cellular effects caused by high glucose. By using these models, we observed additional changes in cell behaviors. First, we observed that high glucose disturbed the distribution of pH3 positive cells in the neuroepithelial cysts. Second, we found that high glucose exposure caused a relatively smaller actin inner boundary enclosed area, which was unlikely due to osmolarity changes. We further investigated key glucose metabolic enzymes in our models and the results showed that the distribution of hexokinase1 (HK1) was affected by high glucose. Under normal conditions HK1 has an apical-basal polarized distribution and is highest next to actin at the boundaries. HK1 was more diffusely distributed and less polarized under high glucose condition. Together, our observations broaden the cellular effects that may result from high glucose in the developing neural tube, especially in the secondary neurulation process.